What Are the Applications of AI in Cardiac Rehabilitation? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Cardiac rehabilitation (CR) is a comprehensive, multidisciplinary program designed to improve the physical, psychological, and social well-being of individua...
Keywords: AI in Cardiology; Applications; Cardiac; Rehabilitation; Artificial Intelligence; Healthcare